Un bilan intermédiaire du Programme de villes nouvelles au Maroc - Jean-Marie Ballout (Les Cahiers d’EMAM)
More than a decade after the launch of a “new towns Program” in Morocco by the Ministry of Housing and Town Planning (2004), the purpose of our article is to provide an overview of this policy. To do this, three inputs are borrowed. First, it is to check whether the terms of its genesis, the powers of its initiator and responsible for project management, ad hoc arrangements (legal and institutional) engaged have given these officials the ability to lead this program efficiently. Second, the ambitious objectives announced and carried by the official discourse, particularly with regard to demographics, urbans and environmentals aspects are related to their current realities. Finally, the conflicts that reveal when conducting projects in the program are analyzed as indicators of malfunctioning governance.